Can a low-threshold check-up motivate older adults to schedule a dental visit? Study protocol for a randomized controlled trial - Aster De Vleeschauwer; Louise Poppe; Roos Colman; Barbara Janssens (Trials)
Abstract Background Most oral diseases benefit from early detection by dental professionals. However, in the older population, regular dental attendance is low. This trial investigates whether a low-threshold check-up by a dental professional in a non-dental setting can motivate older persons to seek professional oral care. Methods A total of 194 community-dwelling persons aged 65 years and older, without a dental check-up over the last 12 months, will be recruited for this randomized, controlled, two-arm, single-blinded, superiority trial with a 1:1 allocation ratio. The intervention group will receive an oral examination including tailored oral health information. They will also be informed about the importance of regular dental visits and will be provided with referral letters for the dental professional and the family physician and a list of nearby dentists. In the control group, the oral examination including tailored information will not be performed. This group will only receive flyers with general oral hygiene information and a list of nearby dentists. The primary outcome is whether or not the participants will contact a dental professional within four months after the intervention. Discussion This study examines the efficacy of a low-threshold dental check-up intervention to motivate older adults to contact a dental professional and reactivate them into primary oral care, addressing barriers to oral care such as low health literacy, subjective treatment need, and dental anxiety. Key strategies include enhancing oral health knowledge, identifying existing oral issues, and involving family physicians. The study, set to run from April 2024 to March 2025, aims to inform future evidence-based oral health promotion strategies for community-dwelling older adults. Trial registration ClinicalTrials.gov NCT06341959. Registered on 25 April 2024.